Relevansi Nilai Dividend Yield dan Price Earnings Ratio (PER) dalam Penilaian Harga Saham Bagi Perusahaan yang Mengalami Pertumbuhan (Studi pada Perusahaan Manufaktur di BEJ Tahun 2001-2005) - I Ketut Jati; Ni Luh Supadmi (Universitas Negeri Surabaya, 2018)
The aim of this research are developed and tested model of market appraiser with first prediction is a equities value.It was a function of book value, rented earning and deviden . This function broaded using proction IOS of company growth level to know value relevation of devidend yield value and price earning ratio (PER) in orther to appariser stock price.Further more , model which used in this research are devidend and rented earning already reflection of using devidend yield and price earning ratio by stock market agentIn addition, the main problem of this research was, How is a relevantion between company growth value, devidend yield, and PER in orther to appraiser stock price?. How is company growth has influnce toward relevantion of dividend yield value and PER in orther to appraiser stock price . The aim of this research is to know are there any influence of relevantion between company growth value , dividend yield and PER in orther to appraiser stock price and to know are there any influence of company growth toward relevantion value dividence yield and PER in orther to appraiser stock price .This research using proposive sampling technique and respondance are manufacture company listed in Jakarta stock exchange during 2001 2005. Data analysis using multiple regretion technique with price and model return . To get just one value so this research using factor analysis because IOS as a proction company growth .Base on price models, result analysis show company growth , devidend yield and PER , all together and partial have relation or relevantion with stock price.Relevantion of devidend yield value and PER in apparaiser stock price has not influence of company growth level . In other hand, model return show that company growth, devidend yield and PER has not value relevantion in appraiser stock price . It has related with stale component and accounting recognition lag which as application in return modelIn conclusion, using alpha 5%, company growth, devidend yield and PER has relevantion value in appraiser stock price . But,company growth has not a basic of relevantion devidend yield value and PER in orther to appraiser stock price for stock market agent . PER for appraiser stock price with stock agent in stock exchange market in Jakarta during 2001 2005. Disclosure of company growth with any eforts from emitance be desirable that being relevant information for any capital stock market i Indonesia.